MON-588 Characteristics of Overt Thyrotoxicosis When TSH Is Measured in All Patients in Nonsurgical Departments - Bashkin, Amir (J Endocr Soc, 2019)
Introduction: Thyroid dysfunction in patients in non-surgical departments is common and often caused by nonthyroidal illness syndrome (NTIS) and medications. The aim of this study was to characterize overt thyrotoxicosis when TSH is measured routinely in medical departments. Methods: This is a retrospective study of adult patients from medical departments, who were admitted to our medical center for any reason. TSH level was measured on admission routinely in all patients, FT3 and FT4 levels were measured in patients with low TSH. In order to characterize the patients with overt thyrotoxicosis, three groups were defined and compared: 1) T4 group: overt thyrotoxicosis with high FT4 included a random sample of patients who had low TSH and only high FT4 levels. 2) T3 group: overt thyrotoxicosis with high FT3 included all patients with low TSH and high FT3 levels (with and without high FT4 levels). 3. NTIS group: Included a random sample of patients with low TSH and FT3 levels and FT4 levels below the middle of the normal range. Results: TSH levels were measured on admission in 77,147 inpatients and 82 (0.11%) patients met the criteria for T3 group. The T4 and the NTIS groups included a random sample of 123 patients and 119 patients respectively. The T4 group was 5.1 times more prevalent than the T3 group. The T3 group had much more elevated FT3 level compared to FT4 elevation in T4 group, 85.4% of the patients in T4 group had FT4 level less than 1.25 times the upper normal level. In addition, the T4 group had low FT3 levels, 79.7% of patients had FT3 levels in the lower half of the norm and less. Compared to the T3 group, the T4 group was older, had less supraventricular arrhythmia, more systemic or inhaled corticosteroids treatment and higher CRP levels (all p<0.001). Compared to the NTIS group, the T4 group had more levothyroxine treatment (p<0.001), more amiodarone treatment (p=0.04) and more women (p=0.009). There were no differences between the T4 and NTIS groups in age, CRP levels, systemic or inhaled corticosteroids treatment and supraventricular arrhythmia. The proportion of patients treated with anti-thyroid drugs was higher in the T3 group than in NTIS and FT4 groups (p <0.001; p= 0.087, 2-sided, p=0.052 1-sided respectively). The NTIS group and the T4 group had no correlation between FT4 and FT3 levels but the T3 group had a borderline positive correlation (r=0.208, p=0.061). T3 group had no correlation between CRP and FT3 levels but T4 and NTIS groups had a negative correlation (r =-0.366, p <0.001; r=-0.270, p=0.03 respectively). Conclusion: When TSH level is measured routinely in non surgical departments, more than 80% of cases that met overt thyrotoxicosis definition were caused by solitary increase in FT4 levels. This T4 group was a result of acute disease and treatment with levothyroxine, corticosteroids, and amiodarone, and in contrast to the T3 group, was rarely related to endogenous excess of thyroid hormones.